CE: Original Research. Issue 7 (July 2018) - Baumgartner, Laura; Townsend, Nicole; Winkelman, Katie; MacLaren, Robert
Abstract : N/A: Objective: Traditional analgesic regimens often fail to control the severe pain patients experience during burn wound care, and the drugs are frequently administered at doses that can cause oversedation and respiratory depression. Ketamine may be an ideal agent for adjunctive analgesia in such patients because of its unique mechanism of action and lack of association with respiratory depression. This study evaluated the efficacy and safety of a critical care RN–driven protocol for IV ketamine administration during burn wound care. Methods: This retrospective cohort study examined all adult burn patients who received ketamine as part of a critical care RN–driven ketamine protocol for burn wound care from September 2011 through September 2013. Efficacy outcomes were opioid and benzodiazepine requirements (expressed as fentanyl and midazolam equivalents, respectively) four hours after ketamine administration compared with four hours before such administration. Safety parameters assessed were neurologic, hemodynamic, and respiratory effects. Results: Twenty-seven patients received 56 ketamine doses as part of this protocol; the mean (SD) dose was 0.75 (0.35) mg/kg. Twenty patients (74%) were male and seven (26%) were female; mean age was 39 years. The average percentage of total body surface area burned was 23.4%. With the protocol, opioid and benzodiazepine requirements were reduced by 29% and 20%, respectively. One patient experienced an episode of oversedation after concomitant administration of ketamine and fentanyl. No patients experienced neurologic or hemodynamic complications following ketamine administration. Conclusions: The administration of ketamine during burn wound care using a critical care RN–driven protocol was associated with reduced opioid and benzodiazepine requirements and few adverse effects. Prospective studies are needed to investigate additional patient outcomes and the independent administration of ketamine by critical care RNs. Abstract : Because of its unique mechanism of action and lack of association with respiratory depression, ketamine may be an ideal agent for adjunctive analgesia in burn patients. The authors of this study evaluated the efficacy and safety of a practice protocol allowing critical care RNs to independently administer IV ketamine for burn wound care.